2005
DOI: 10.1002/jor.20039
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis and human herpes virus 6 (HHV‐6), an analysis by real‐time polymerase chain reaction

Abstract: Patients with Langerhans cell histiocytosis (LCH) usually present to orthopedic surgeons because this disease most commonly affects bone. The pathogenesis of LCH is unknown, although roles for environmental, infectious, immunologic, and genetic causes have been postulated. More specifically, there is limited data suggesting that human herpes virus 6 (HHV‐6) may be a potential etiologic agent. Frozen biopsy material was obtained from 13 patients with LCH and 20 patients without the disease. After ensuring histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
(85 reference statements)
2
3
1
Order By: Relevance
“…However the viral load was very low, and the virus was not detectable by immunochemistry suggesting that HHV-6 infection is quiescent. Together with our serological data and serum PCR, and in the light of the study of Glotzbecker et al, [31] who found a similar frequency PCR positive samples in LCH granuloma and control tissues, we hypothetize that HHV6 do not productivey infect LC in vivo and may be carried by bystander lymphocytes which are present in the granuloma.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However the viral load was very low, and the virus was not detectable by immunochemistry suggesting that HHV-6 infection is quiescent. Together with our serological data and serum PCR, and in the light of the study of Glotzbecker et al, [31] who found a similar frequency PCR positive samples in LCH granuloma and control tissues, we hypothetize that HHV6 do not productivey infect LC in vivo and may be carried by bystander lymphocytes which are present in the granuloma.…”
Section: Discussionsupporting
confidence: 86%
“…We think that our results therefore resolve the much debated issue of the role of EBV in the pathogenesis of LCH [19], [21], [22], [30], [31]. Because EBV infected B cells are present in the blood of healthy seropositive individuals [40] at a low frequency in the order of 10- 6 [41] it is not unexpected to find a small number of EBV infected B cells in LCH granuloma, which contains B cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, our findings of a low incidence in Blacks are not fully supported by an infectious theory, as literature also reports low vaccination coverage for black children, although disparities between whites non‐Hispanic and blacks non‐Hispanic have narrowed in the period of 2001–2010 . It is important to clarify that although two studies have demonstrated associations between infections, lack of immunizations, and LCH , other studies failed to show a possible viral etiology for the disease .…”
Section: Discussioncontrasting
confidence: 80%
“…Various factors have been indicated, such as tuberculosis, lipid metabolism disorders, infections and immunity disorders, genetic and environmental factors. Although some studies established an association between human herpesvirus type 6 (HHPV6) (21) and LCH, others failed to prove increased prevalence of HHPV6 in the tissues of patients with LCH in regard to healthy population (22). It was also found that there was no causal role for HHV8 in the etiology of LCH (23), as well as the other eight viruses (24): herpes simplex virus, cytomegalovirus, Epstein Barr virus, adenoviruses, T-cell lymphotropic type I and type II virus, human immunodefi ciency virus (HIV) and parvovirus.…”
Section: Discussionmentioning
confidence: 99%